Ketersediaan Sumber Daya Manusia Kesehatan pada Fasilitas Kesehatan Tingkat Pertama dalam Era Jaminan Kesehatan Nasional di Delapan Kabupaten-Kota di Indonesia - Mujiati, Mujiati; Yuniar, Yuyun (Media Penelitian dan Pengembangan Kesehatan, 2016)
Implementation of the National Health Insurance program causes various effects, including an increased number of visits to primary health facilities, so it takes an adequate distribution of human resources.The aims of this study is to describe the availability of human resources for health in primary health centers in the era of National Health Insurance. Type of research is quantitative-qualitative method withcross sectional approach. Data collecting has done by interviews and round table discussion. Researchlocations were selected purposively in eight districts/cities, namely Bekasi City and Bogor District (WestJava), South Tangerang City and Serang District (Banten), Yogyakarta City and Bantul District (DIY),Surakarta City and Sragen District (Central Java). Informants are leaders/representatives of primaryhealth centers, clinics, physicians and the district/city health office. The quantitative data were analyzed descriptively and qualitative data using content analysis. Health centers in eight districts/cities do notall have the human resources for health in accordance of Permenkes RI No. 75/2014, but general practitioners, midwives and nurses have been available in all health centers though the amount isstill lacking. With the exception of Bogor, the number of medical personnel throughout the clinic is inconformity with Permenkes RI No. 9/2014, but other types of human resources for health is still a lot thatÂ has not been available. Meanwhile, throughout the medical practitioners, the most human resources widely available are general practitioners and nurses. There are changes in procurement planning ofhuman resources in the era of National Health Insurance, increased workload and working hours, sothat it is needed planning and procurement of human resources based on needs.Keywords: human resources, primary health facilities, national health insuranceAbstrakPelaksanaan program Jaminan Kesehatan Nasional (JKN) menimbulkan berbagai dampak, termasuk meningkatnya jumlah kunjungan ke Fasilitas Kesehatan Tingkat Pertama (FKTP), sehingga dibutuhkan sumber daya manusia (SDM) kesehatan yang memadai. Tujuan penelitian adalah untuk memberi gambaran tentang ketersediaan SDM kesehatan di FKTP dalam era JKN. Jenis penelitian adalah kuantitatif-kualitatif dengan pendekatan cross sectional. Pengumpulan data dengan wawancara dan round table discussion. Lokasi penelitian dipilih secara purposive di 8 kabupaten/kota yaitu Kota Bekasi dan Kabupaten Bogor (Jawa Barat), Kota Tangerang Selatan dan Kabupaten Serang (Banten), KotaYogyakarta dan Kabupaten Bantul (DIY), serta Kota Surakarta dan Kabupaten Sragen (Jawa Tengah). Informan yaitu pimpinan/wakil institusi puskesmas, klinik, dan praktik dokter serta dinas kesehatan kabupaten/kota. Analisa data kuantitatif dilakukan secara deskriptif dan analisa data kualitatif dengan content analysis. Puskesmas di 8 kabupaten/kota belum seluruhnya memiliki SDM kesehatan sesuaiPermenkes RI Nomor 75 tahun 2014, namun dokter umum, bidan dan perawat telah tersedia di seluruh puskesmas meskipun dengan jumlah yang masih kurang. Kecuali Kabupaten Bogor, jumlah tenaga medis di seluruh klinik sudah sesuai Permenkes RI Nomor 9 Tahun 2014, namun jenis SDM kesehatan lain masih banyak yang belum tersedia. Sedangkan di seluruh praktik dokter, SDM kesehatan yangpaling banyak tersedia yaitu dokter umum dan perawat. Terdapat perubahan dalam perencanaan pengadaan SDM di daerah sesudah JKN, peningkatan beban kerja dan jam kerja, sehingga diperlukan perencanaan dan pengadaan SDM berbasis kebutuhan.Kata Kunci: SDM, FKTP, JKN